On human persons - Petrus, Klaus, 1967- (Metaphysical research, 2003)
There is no question: We are all persons. But what exactly are persons? Are we immaterial souls or Cartesian Egos which only contingently have bodies? Or are persons nothing over and above their bodies? Are they essentially or most fundamentally animals, evolved beings of a certain sort? Or are we something other or more than animals, namely constituted beings with a certain capacity that distinguishes persons from everything else? What is necessary, and what is sufficient, for an entity to be classified or (re- )identified as a person? What's the value of an analysis of such (biological or psy.